2016
DOI: 10.5005/jp-journals-10024-1977
|View full text |Cite
|
Sign up to set email alerts
|

New Single-bottle Ceramic Primer: 6-month Case Report and Laboratory Performance

Abstract: Introduction:This article presents a 6-month case report and an in vitro evaluation of the performance of the new self-etching glass-ceramic monobond etch and prime (MEP) when applied in a lithium disilicate (LD). The MEP contains in the same bottle, along with acid conditioner and silanes. This simplifies the bonding procedures by reducing not only the number of steps, but also the working time. A 42-year-old female patient sought for esthetic treatment, and the main complaint was the darkened appearance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 22 publications
3
28
0
1
Order By: Relevance
“…The 5% HF acid etch had been used in the two-step conditioning system, which creates low surface roughness. Siqueira et al 21 have also reported that partial dissolution of the glassy phase will be created, when ceramic surfaces were etched by using one step conditioning system. Poor resin cements flow into the micropores could be explained by surface roughness and mechanical interlocking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5% HF acid etch had been used in the two-step conditioning system, which creates low surface roughness. Siqueira et al 21 have also reported that partial dissolution of the glassy phase will be created, when ceramic surfaces were etched by using one step conditioning system. Poor resin cements flow into the micropores could be explained by surface roughness and mechanical interlocking.…”
Section: Discussionmentioning
confidence: 99%
“…The wettability of the ceramic surface for the application of resin composites and silane-coupling agents is affected by this increase in surface roughness. 20,21 The importance of adequately porous surface is observed for the durable cementation of both Fd and Ld ceramic indirect restorations. 24 Clean surfaces, the use of low-viscosity adhesives, cements, and suitable wetting are the other factors that contribute to the effectiveness of bonding between the materials.…”
Section: Discussionmentioning
confidence: 99%
“…Although this shallow etching pattern did not jeopardize immediate bond strength (10,11), it may reduce the longevity of the bond strength of the ceramic interface with the silane agent. Thus, a preliminary etching with hydrofluoric acid before the use of the self-etching ceramic primer could be an alternative to improve the etching pattern and prolong the lifetime of the lithium disilicate bonds.…”
Section: Introductionmentioning
confidence: 90%
“…According to the manufacturer, these novel material reduces the toxic potential of the HF, the chair-time required and the technique sensitivity of etching ceramic when compared to the conventional methods (9). It was shown that the selfetching ceramic primer promotes less-pronounced etching pattern than that produced by the two-step procedure involving hydrofluoric acid and silane (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation